'I'm not a chance taker': A mixed methods exploration of factors affecting prostate cancer treatment decision-making. Issue 8 (17th November 2021) - Owens, Otis L.; Estrada, Robin M.; Johnson, Kim; Cogdell, Micheal; Fried, Daniel B.; Gansauer, Lucy; Kim, Simon
ABSTRACT : Objectives: African American prostate cancer survivors experience post-treatment decisional regret more often than European Americans, which can lead to negative long-term effects on quality of life. A prominent driver of health-related decision-making is emotion, yet little work has examined the impact emotions may have on decisional regret. The goal of this study was to explore experiences, perceptions, and emotions of prostate cancer survivors in relation to their diagnostic and treatment decision-making processes, prostate cancer treatment, and outcomes. Additionally, we sought to identify factors that might explain differences in prostate cancer outcomes between African and European Americans. Design: This mixed-methods study utilized a convergent parallel design, in which quantitative and qualitative data were collected simultaneously and then integrated to more robustly explain relationships between variables. Survivors were eligible for the study if they had been previously diagnosed with localized prostate cancer and were no more than six months post-treatment. The study was guided by the Risk as Feelings Model, which predicts the relationship between emotion and cognition in high-risk decision-making. Results: No men experienced decisional regret following treatment, even if they experienced side effects. While all men reported being surprised about their prostate cancer diagnosis, strong negative emotions were more common among men under 65. Family support and spirituality appeared to mitigate negative emotions. Perceived authenticity of provider communication was the most influential mediator in men's decision-making and positive perceptions of their outcomes. Conclusions: To mitigate the impact emotional responses have on decision-making and post-treatment regret, providers should explore alternate therapies (e.g. counseling for men diagnosed with prostate cancer at a young age) and include family members in prostate cancer treatment discussions. Most importantly, providers should be aware of the importance of quality communication on men's cognitive and emotional processes and their perceptions of treatment outcomes.